Glossolalia Sebagai Karunia Roh Yang Berlanjut: Rekonstruksi Biblika-Historis Atas Bahasa Roh Dalam Apologetika Pentakosta - Pasaribu, George Rudi Hartono; Rumaijuk, Stefan; Antonius, Yosef (LPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
This article examines the biblical basis, history of interpretation, and Pentecostal defense of glossolalia as a continuing gift of the Spirit. Using qualitative library research with exegetical, historical-theological, and apologetic approaches, it distinguishes glossolalia from xenolalia and clarifies that the Indonesian expression bahasa roh is a theological designation rather than a literal Greek phrase. The study argues cumulatively that the New Testament gives no explicit terminus for tongues at the close of the apostolic age, locates the cessation of partial gifts within an eschatological horizon, and regulates rather than prohibits their use. Historical reception reveals continuity and change, while selected official GBI documents and publicly documented teaching associated with Niko Njotorahardjo and Kong Hee illustrate the continuing reception of the practice in contemporary Pentecostal communities. On this basis, the article affirms that glossolalia should be received, taught, and given responsible space in the church today, both as personal prayer and, with interpretation, for congregational edification. Such affirmation does not validate every manifestation or permit coercion; the practice remains subject to Christological confession, Scripture, love, self-control, ecclesial order, communal discernment, and the fruit of the Spirit. Because this study is library-based and limited to selected biblical, historical, and ecclesial sources, it does not empirically verify the authenticity, linguistic structure, or pastoral outcomes of particular manifestations. Further multi-site fieldwork, linguistic analysis, and comparative denominational research are therefore required.